2014
DOI: 10.1057/ajp.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, Tact and the Freedom to be Natural

Abstract: This paper explores the concepts of tact and empathy in the context of the Freud-Ferenczi correspondence around Ferenczi's "The Elasticity of Psycho-Analytic Technique" paper. It goes on to explore the problems that they encounter in the neighborhood of reconciling science and subjectivity, in relation to the work on personal knowledge of the Hungarian philosopher Michael Polanyi and concludes with some implications for psychoanalytic training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a review of the correspondence between Freud and Ferenczi on the issue of tact, Robinson (2014) suggested that, "Taken together empathy, tact and being natural speak of the analyst's freedom to use himself beyond the level of consciousness in the process of analysis: his bodily self in the empathy; his unconscious as a receiving instrument for the patient's unconscious; his evenly suspended attention as complimentary [sic] to the patient's free association" (p. 334). However, despite its ubiquity in clinical practice, clinical tact-like therapist dishonesty-has remained largely absent from recent literature, likely due to the subject's complicated and highly subjective nature.…”
Section: Possible Motives Of Therapist Dishonestymentioning
confidence: 99%
“…In a review of the correspondence between Freud and Ferenczi on the issue of tact, Robinson (2014) suggested that, "Taken together empathy, tact and being natural speak of the analyst's freedom to use himself beyond the level of consciousness in the process of analysis: his bodily self in the empathy; his unconscious as a receiving instrument for the patient's unconscious; his evenly suspended attention as complimentary [sic] to the patient's free association" (p. 334). However, despite its ubiquity in clinical practice, clinical tact-like therapist dishonesty-has remained largely absent from recent literature, likely due to the subject's complicated and highly subjective nature.…”
Section: Possible Motives Of Therapist Dishonestymentioning
confidence: 99%